Thermophysics Simulation of Laser Recrystallization of High-Ge-Content SiGe on Si Substrate - Chao Zhang; Jianjun Song; Jie Zhang; Shulin Liu (Advances in Condensed Matter Physics)
The high-Ge-content SiGe material on the Si substrate can be applied not only to electronic devices but also to optical devices and is one of the focuses of research and development in the field. However, due to the 4.2% lattice mismatch between Si and Ge, the epitaxial growth of the high-Ge-content SiGe epitaxial layer directly on the Si substrate has a high defect density, which will seriously affect the subsequent device performance. Laser recrystallization technique is a fast and low-cost method to effectively reduce threading dislocation density (TDD) in epitaxial high-Ge-content SiGe films on Si. In this paper, by means of finite element numerical simulation, a 808 nm laser recrystallization thermal physics model of a high-Ge-content SiGe film (for example, Si0.2Ge0.8) on a Si substrate was established (temperature distribution physical model of Si0.2Ge0.8 epitaxial layer under different laser power, Si0.2Ge0.8 epitaxial layer thickness, and initial temperature). The results of this paper can provide important technical support for the preparation of high-quality high-Ge-content SiGe epilayers on Si substrates by laser recrystallization.